Impact of specific postoperative complications on the outcomes of emergency general surgery patients. Issue 5 (May 2015) - McCoy, Christopher Cameron; Englum, Brian R.; Keenan, Jeffrey E.; Vaslef, Steven N.; Shapiro, Mark L.; Scarborough, John E.
<x xml:space="preserve">Abstract</x> BACKGROUND The relative contribution of specific postoperative complications on mortality after emergency operations has not been previously described. Identifying specific contributors to postoperative mortality following acute care surgery will allow for significant improvement in the care of these patients. METHODS Patients from the 2005 to 2011 American College of Surgeons' National Surgical Quality Improvement Program database who underwent emergency operation by a general surgeon for one of seven diagnoses (gallbladder disease, gastroduodenal ulcer disease, intestinal ischemia, intestinal obstruction, intestinal perforation, diverticulitis, and abdominal wall hernia) were analyzed. Postoperative complications (pneumonia, myocardial infarction, incisional surgical site infection, organ/space surgical site infection, thromboembolic process, urinary tract infection, stroke, or major bleeding) were chosen based on surgical outcome measures monitored by national quality improvement initiatives and regulatory bodies. Regression techniques were used to determine the independent association between these complications and 30-day mortality, after adjustment for an array of patient- and procedure-related variables. RESULTS Emergency operations accounted for 14.6% of the approximately 1.2 million general surgery procedures that are included in American College of Surgeons' National Surgical Quality Improvement Program but for 53.5% of the 19, 094 postoperative deaths. A total of 43, 429 emergency general surgery patients were analyzed. Incisional surgical site infection had the highest incidence (6.7%). The second most common complication was pneumonia (5.7%). Stroke, major bleeding, myocardial infarction, and pneumonia exhibited the strongest associations with postoperative death. CONCLUSION Given its disproportionate contribution to surgical mortality, emergency surgery represents an ideal focus for quality improvement. Of the potential postoperative targets for quality improvement, pneumonia, myocardial infarction, stroke, and major bleeding have the strongest associations with subsequent mortality. Since pneumonia is both relatively common after emergency surgery and strongly associated with postoperative death, it should receive priority as a target for surgical quality improvement initiatives. LEVEL OF EVIDENCE Prognostic and epidemiologic study, level III.